Do institutions receive comparable execution in the NYSE and Nasdaq markets? A transaction study of block trades - LaPlante, Michele; Muscarella, Chris J. (Journal of Financial Economics, 1997)
The trading structure differences between the NYSE and the Nasdaq market could produce different levels of trading liquidity. Several studies have attempted to measure these differences by comparing bid-ask spreads. This paper uses an alternative approach to compare liquidity. We analyze three issues: (1) the frequencies of the sizes and types of block trades found in the two markets, (2) the immediate price effects of the block transactions, and (3) the temporary and permanent price effects of the blocks. We find evidence that the NYSE system provides more liquidity for block transactions.